2005
DOI: 10.1002/eqe.522
|View full text |Cite
|
Sign up to set email alerts
|

Effect of isolator and ground motion characteristics on the performance of seismic-isolated bridges

Abstract: SUMMARYThis paper presents the e ect of isolator and substructure properties as well as the frequency characteristics and intensity of the ground motion on the performance of seismic-isolated bridges (SIBs) and examines some critical design clauses in the AASHTO Guide Speciÿcation for Seismic Isolation Design. For this purpose, a parametric study, involving more than 800 non-linear time history analyses of simpliÿed structural models representative of typical SIBs, is conducted. The results from the parametric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…Furthermore, the characteristic strength, Q d , of the isolators is varied to obtain typical Q d /W ratios ranging between 0.025 and 0.15 where W is the tributary weight acting on the isolator. The effect of the isolator's elastic stiffness on the performance of seismic-isolated structures has been found to be negligible earlier [1,24]; hence, it is not considered in this study. In addition to the parameters defined above, the analysis results are also presented using two of the four dimensionless terms proposed in [23,24] to completely describe the response of a structural system with bilinear force-deformation relationship in relation to the characteristics of an NF, pulse-type excitation.…”
Section: Types Of Analyses Conducted and Parameters Consideredmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, the characteristic strength, Q d , of the isolators is varied to obtain typical Q d /W ratios ranging between 0.025 and 0.15 where W is the tributary weight acting on the isolator. The effect of the isolator's elastic stiffness on the performance of seismic-isolated structures has been found to be negligible earlier [1,24]; hence, it is not considered in this study. In addition to the parameters defined above, the analysis results are also presented using two of the four dimensionless terms proposed in [23,24] to completely describe the response of a structural system with bilinear force-deformation relationship in relation to the characteristics of an NF, pulse-type excitation.…”
Section: Types Of Analyses Conducted and Parameters Consideredmentioning
confidence: 98%
“…In the case of SIBs subjected to far-field ground motions, the isolator displacements generally have manageable magnitudes [1]. However, for SIBs subjected to near-fault (NF) ground motions with directivity effect, the isolator displacements tend to be considerably large [2][3][4][5] due to intense, long-duration velocity pulses associated with such ground motions.…”
Section: Diclelimentioning
confidence: 99%
See 1 more Smart Citation
“…As for the effect of the frequency characteristics and its influence on the seismic response of base-isolated systems and on the optimal isolator properties, other studies (e.g., [27]- [29]), concerning isolated buildings and bridges, demonstrated that soft soil condition leads to a great alteration of the variances with large increment of the peak ratios, in terms of displacements and shear forces, by negatively affecting the isolated systems. Similarly, Kulkarni and Jangid [30] analyzed the effects of superstructure flexibility on the response of base-isolated structures subjected to non-stationary random processes by comparing the stochastic response of a base-isolated structure with superstructure modelled as flexible and rigid and highlighting that the seismic isolation is more effective for firm or rock type soil than the soft soils.…”
Section: Introductionmentioning
confidence: 99%
“…Dicleli and Mansour [7] have studied the economic and structural efficiency of the friction pendulum device (FPD) application for retrofitting typical seismically vulnerable bridges in the State of Illinois. Moreover, the effects of ground motion characteristics on the dynamic response and performance of seismically isolated bridges have been evaluated by some authors [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%